An Analysis of Using Code Switching by the Students in Learning English as a Foreign Language at MA Al Fatah Kota Mulya - Dwi Andriani; Eka Agustina; Fahita Al Afiyah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to describe the types of code switching that occur in English language learning at MA Al Fatah Kota Mulya in four meetings. This type of research is descriptive-qualitative research. The subjects of this research were the eleventh-grade students. The object of this research is a speech on the use of code switching, which includes the types of code switching in English language learning at MA Al Fatah Kota Mulya. The results of the research show that there are 8 types of code switching in English language learning at MA Al Fatah Kota Mulya. Furthermore, all data is divided into 3 types of code switching: (1) intra-sentential switching occurred in 1 data (12,5%), (2) inter-sentential switching occurred in 3 data (37,5%), and (3) tag switching occurred in 4 data (50%). So, the most dominant type of code switching is tag switching.